2020
DOI: 10.1161/circresaha.119.316053
|View full text |Cite
|
Sign up to set email alerts
|

Global Reach 2018 Heightened α-Adrenergic Signaling Impairs Endothelial Function During Chronic Exposure to Hypobaric Hypoxia

Abstract: Rationale: Chronic exposure to hypoxia is associated with elevated sympathetic nervous activity and reduced vascular function in lowlanders, and Andean highlanders suffering from excessive erythrocytosis (EE); however, the mechanistic link between chronically elevated sympathetic nervous activity and hypoxia-induced vascular dysfunction has not been determined. Objective: To determine the impact of heightened sympathetic nervous activity on resistance a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
40
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 30 publications
(43 citation statements)
references
References 68 publications
2
40
0
Order By: Relevance
“…Unexpectedly, the absolute and relative circulatory responses were the same between sea level and high altitude in lowlanders; such findings were, however, consistent with the similar indexes of CCA stiffness that were observed. These data indicate that the CCA diameter response to the CPT might not accurately represent vascular ‘health’ at high altitude, because other established methods of vascular function, such as brachial artery flow‐mediated dilatation (Tremblay et al., 2018) or the forearm vascular response to acetylcholine (Tymko et al., 2020b), have demonstrated that vascular function is reduced at high altitude >4000 m a.s.l. in healthy lowlanders (also reviewed by Tymko et al., 2019).…”
Section: Discussionmentioning
confidence: 96%
“…Unexpectedly, the absolute and relative circulatory responses were the same between sea level and high altitude in lowlanders; such findings were, however, consistent with the similar indexes of CCA stiffness that were observed. These data indicate that the CCA diameter response to the CPT might not accurately represent vascular ‘health’ at high altitude, because other established methods of vascular function, such as brachial artery flow‐mediated dilatation (Tremblay et al., 2018) or the forearm vascular response to acetylcholine (Tymko et al., 2020b), have demonstrated that vascular function is reduced at high altitude >4000 m a.s.l. in healthy lowlanders (also reviewed by Tymko et al., 2019).…”
Section: Discussionmentioning
confidence: 96%
“…53 Evidence derived from studies of adult men at high altitude has established that exposure to chronic hypoxia induces endothelial dysfunction mediated in part through heightened adrenergic vasoconstrictor signaling. 54 This effect of chronic hypoxia on adrenergic pathways innervating peripheral blood vessel resistance can be triggered early in life, leading to heightened adrenergic vasoconstrictor signaling in the embryonic or fetal periods, [55][56][57][58] as well as permanently in adult offspring. 13,59,60 For instance, chronically hypoxic fetal sheep have enhanced plasma catecholamine and α 1adrenergic peripheral vasoconstrictor responses to acute stress.…”
Section: Discussionmentioning
confidence: 99%
“…Hypoxaemia and polycythaemia may affect arterial blood pressure through sympathetic hyperactivity (Tymko et al, 2020b), increased peripheral vascular resistance, decreased endothelial function via altered vascular shear stress (de Simone et al, 1990) or increased adrenergic signalling, all of which increase the risk of hypertensive disease (Corante et al, 2018). As reported previously by our group using the microneurographic technique (Tymko et al, 2020b), MSNA burst frequency (P = 0.035) and burst incidence (P = 0.013) were higher in the semi-recumbent position in CMS+ compared with healthy Andeans (Fig. 3A-C).…”
Section: Assessment Of Resting Blood Pressure and Vascular Shear Stressmentioning
confidence: 99%